The Prevalence Of Odontogenic Pathology In Patients With Bilateral Rhinosinusitis (Journal of Pharmaceutical Negative Results, 2023)
Objective: We investigated cases with opacification on maxillary sinus computed tomography (CT)/ orthopantomography (OPG) among patients with rhinosinusitis with opacification in both paranasal sinuses (bilateral rhinosinusitis) to confirm the involvement of odontogenic infections.Methods: This study included 75 patients who were diagnosed with bilateral rhinosinusitis based on clinical examination and evident opacification on at least one side on maxillary sinus imaging with computed tomography CT/ orthopantomography (OPG). The definition of odontogenic sinusitis was determined by examining EPT and oral findings, in addition to the CT/ orthopantomography (OPG), by one dental surgeon and one otolaryngologist.Results: From the present study it was found that 45.3% of patients had odontogenic infections, which were associated with multiple infected teeth in some cases. Odontogenic infection was observed in both sinuses in some patients. Sinusitis with polyps was frequently associated with dental infection, and some cases were also associated with mycosis. Almost no oral symptoms were observed.Conclusions: The results suggest that clinicians should consider odontogenic infection in patients with rhinosinusitis with opacification, on at least one side on maxillary sinus imaging. This means that accurate diagnosis may be challenging for otolaryngologist or dentists alone, suggesting that collaboration between the two would be suitable for this task.